Introductory Statistics - Illowsky, Barbara; Dean, Susan; Chiappetta, Laurel; Open Textbook Library (Open Textbook Library, 2013)
Introductory Statistics follows the scope and sequence of a one-semester, introduction to statistics course and is geared toward students majoring in fields other than math or engineering. This text assumes students have been exposed to intermediate algebra, and it focuses on the applications of statistical knowledge rather than the theory behind it. The foundation of this textbook is Collaborative Statistics, by Barbara Illowsky and Susan Dean, which has been widely adopted. Introductory Statistics includes innovations in art, terminology, and practical applications, all with a goal of increasing relevance and accessibility for students. We strove to make the discipline meaningful and memorable, so that students can draw a working knowledge from it that will enrich their future studies and help them make sense of the world around them. The text also includes Collaborative Exercises, integration with TI-83,83+,84+ Calculators, technology integration problems, and statistics labs. OpenStax College has compiled many resources for faculty and students, from faculty-only content to interactive homework and study guides.
Sampling and Data -- Descriptive Statistics -- Probability Topics -- Discrete Random Variables -- Continuous Random Variables -- The Normal Distribution -- The Central Limit Theorem -- Confidence Intervals -- Hypothesis Testing with One Sample -- Hypothesis Testing with Two Samples -- The Chi-Square Distribution -- Linear Regression and Correlation -- F Distribution and One-Way ANOVA
In English.
Description based on print resource
Keywords: Mathematics -- Textbooks; Applied mathematics -- Textbooks